THE INFLUENCE OF DIGITALISATION ON THE EVOLUTION OF MARKETING STRATEGIES IN THE POST-PANDEMIC ERA: A LITERATURE REVIEW - Kowiyanto Kowiyanto; Yoan Santosa Putra (Adisam Publisher, 2025)
The COVID-19 pandemic has triggered an acceleration in digital transformation, with a significant impact on the evolution of marketing strategies. This study explores the influence of digitalisation on marketing strategies in the context of the post-pandemic era, focusing on changes in consumer behaviour and the strategic responses adopted by companies. The literature review method was used to collect and analyse data from various sources, including books, journals and other documents. The research findings show that digitalisation has driven innovation in marketing strategies, including the increased use of social media, digital content marketing, e-commerce, and technology- based solutions such as artificial intelligence (AI) for personalisation. In addition, the research revealed the importance of adopting an omnichannel approach to create a seamless customer experience between online and offline channels. The implementation of big data analytics and predictive technologies to understand and predict consumer behaviour is also becoming more crucial in optimising marketing strategies.